A NUMERICAL APPROACH FOR FAULT DETECTION IN BEAM-LIKE STRUCTURES USING MODAL STRAIN ENERGY (2013)
Vibration-baseddamage detection is based on the fact that measurements of changes in thevibration properties of a structure can be used to determine the occurrence ofstructural damage. Therefore, there is a strong need for the development andimplementation of fault detection and optimum sensor location methods thataddress the issue of limited instrumentation and its effect in predictingdamage degradation. In this paper, the results of a numerical implementation ofa previously developed sensor distribution method are presented. A finiteelement model of a railway box-girder bridge is assembled. Then, the damageindex method is numerically implemented in order to identify damage from theresulting sensor measurements. Both the optimum sensor placement and the damagedetection methods are based on the concept of modal strain energy. Finally, thenumerical results show that the proposed approach is suitable for continuousdamage monitoring implementations and can be used as a useful tool for damageassessment in beam-like structures.